2009
DOI: 10.1093/nar/gkn680
|View full text |Cite
|
Sign up to set email alerts
|

PeroxiBase: a database with new tools for peroxidase family classification

Abstract: Peroxidases (EC 1.11.1.x), which are encoded by small or large multigenic families, are involved in several important physiological and developmental processes. They use various peroxides as electron acceptors to catalyse a number of oxidative reactions and are present in almost all living organisms. We have created a peroxidase database (http://peroxibase.isb-sib.ch) that contains all identified peroxidase-encoding sequences (about 6000 sequences in 940 organisms). They are distributed between 11 superfamilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(73 citation statements)
references
References 14 publications
1
69
0
2
Order By: Relevance
“…Analysis of the genome sequence has revealed that DyPs are mostly present in bacteria, whereas only a limited number exists in fungi and higher eukaryotes (14). DyPs can be subdivided into four types, A, B, C, and D, based on their primary sequences (15). Identities between different types are at most 15%, each having a unique characteristic sequence.…”
mentioning
confidence: 99%
“…Analysis of the genome sequence has revealed that DyPs are mostly present in bacteria, whereas only a limited number exists in fungi and higher eukaryotes (14). DyPs can be subdivided into four types, A, B, C, and D, based on their primary sequences (15). Identities between different types are at most 15%, each having a unique characteristic sequence.…”
mentioning
confidence: 99%
“…Homology sequence searches were performed using BLAST (Altschul et al 1997) against non-redundant (nr) database and class III PeroxiBase (Koua et al 2009). Multiple sequence alignment of plant peroxidases was performed using Clustal X program (Thompson et al 1997).…”
Section: Multiple Sequence Alignment and Phylogenetic Analysismentioning
confidence: 99%
“…Analysis of the amino acid sequence deduced for AP using the databank, PeroxiBase (Koua et al 2009), revealed that A. marina has the highest homology with that of Triphysaria versicolor, N. tabacum, C. roseus, and Capsicum annum. AP also shares significant identity with barley grain peroxidase (BGP) whose 3D structure has been determined (Henriksen et al 1998a).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 10630 peroxidase sequences were recorded in PeroxiBase, and more than 78% of peroxidases are coded for heme peroxidases [4]. According to the phylogenetic trees, heme peroxidases are distributed into 9 In the heme-containing peroxidases, cytochrome c peroxidase, horseradish peroxidase, lactoperoxidase, and myeloperoxidase are of interest due to their wide applications or unique reactions, and thus are intensively studied.…”
Section: Heme Peroxidase and Heme Cofactormentioning
confidence: 99%